Increase in penguin populations during the Little Ice Age in the Ross Sea, Antarctica - Emslie, Steven D.; NC DOCKS at The University of North Carolina Wilmington (2013)
Penguins are an important seabird species in Antarctica and are sensitive to climate and environmental changes. Previous studies indicated that penguin populations increased when the climate became warmer and decreased when it became colder in the maritime Antarctic. Here we determined organic markers in a sediment profile collected at Cape Bird, Ross Island, high Antarctic, and reconstructed the history of Adélie penguin colonies at this location over the past 700 years. The region transformed from a seal to a penguin habitat when the Little Ice Age (LIA; 1500–1800 AD) began. Penguins then became the dominant species. Penguin populations were the highest during ca. 1490 to 1670 AD, a cold period, which is contrary to previous results in other regions much farther north. Different responses to climate change may occur at low latitudes and high latitudes in the Antarctic, even if for same species.